2012
DOI: 10.1308/003588412x13171221502149
|View full text |Cite
|
Sign up to set email alerts
|

Bladder injuries in emergency/expedited laparoscopic surgery in the absence of previous surgery: a case series

Abstract: INTRODUCTION The use of laparoscopy as a diagnostic and therapeutic tool is being used increasingly in the emergency setting with many of these procedures being performed by trainees. While the incidence of iatrogenic injuries is reported to be low, we present six emergency or expedited cases in which the bladder was perforated by the suprapubic trocar. CASES Three cases were related to the management of appendicitis, two to negative diagnostic laparoscopies for lower abdominal pain and one to an ectopic pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 6 publications
0
23
0
1
Order By: Relevance
“…One case involved injury to an urachal cyst [13], one to a possible patent urachus [7] and four cases involved injury to an urachal diverticulum [1,4,5,14]. Our case is the fifth such reported case of injury to an urachal diverticulum due to laparoscopic port insertion.…”
Section: Urachal Abnormalitiesmentioning
confidence: 80%
See 2 more Smart Citations
“…One case involved injury to an urachal cyst [13], one to a possible patent urachus [7] and four cases involved injury to an urachal diverticulum [1,4,5,14]. Our case is the fifth such reported case of injury to an urachal diverticulum due to laparoscopic port insertion.…”
Section: Urachal Abnormalitiesmentioning
confidence: 80%
“…Injury to the urinary bladder due to suprapubic port insertion is rare. Levy et al reported six cases of bladder injury due to suprapubic port placement in 1,671 patients (incidence 0.36%) [4], with one of the six patients having an urachal diverticulum.…”
Section: Complication Rate Of Laparoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Although Levy and colleagues reported only 0.36% (6/1671) of iatrogenic bladder injuries due to laparoscopic secondary port insertions in patients without prior history of abdominal surgery, one of their young patients developed a horrendous complication -gangrene of the abdominal wall (necrotising fasciitis). 25 The authors took into account all the laparoscopic cases (diagnostic and therapeutic), but failed to mention the study period. All but one of these patients underwent temporary preoperative in/out catheterization before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate associated with laparoscopy induced bowel injury is high at 3.6% (9). Reports of other visceral injuries in laparoscopic surgery can be found in the literature and include bladder injuries (11) and splenic injuries (12).…”
Section: Introductionmentioning
confidence: 99%